ANTISLAVERY IMPULSES. (17th November 2015) - ABZUG, ROBERT H.
Abstract : The year 2015 marks not only the sesquicentennial of Appomattox but also the fiftieth anniversary of the publication of Martin Duberman's anthology The Antislavery Vanguard, a collection of essays that set the agenda for an ever-expanding treatment of antislavery that continues to this day. In assessing these new additions to that literature, I began to think about the arc that historians of American abolitionism have traced in the past half-century, and the ways in which Kytle and McDaniel were inheritors and extenders of that historiographical revolution. Duberman defined his purpose as bringing together the work of historians bent on overthrowing a long-prevailing view of abolitionists as "meddlesome fanatics . . . wrapped in their self-righteous fury, who did so much to bring on a needless war." He initially imagined a volume that would debate abolitionist virtue and vice but could find no scholars who would uphold the older stereotype. Instead, his contributors explored themes largely sympathetic to the reformers.